Hearing Aid Fitting Protocols for Adults and Elderly Individuals - Iwahashi, Juliana Harumi; Jardim, Isabela de Souza; Sizenando, Carina Stábile; Bento, Ricardo Ferreira (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The hearing aids are one of the options used in auditory rehabilitation with the objective to improve communication and to minimize the limitations caused by hearing loss. Despite the development of technology, the selection and fitting processes demand specific procedures which goal is to maximize performance, benefit and user' satisfaction.Aim: To describe the hearing aid selecting and fitting protocol for adults and the elderly in an audiological center, which development was based on previously described and validated protocols from the specific literature and information based on clinical practice.Conclusions: The Hearing Aid Selecting and Fitting Protocol for adults and elder subjects showed that a greater amount of collected information provides better expectations for the patients' real life and greater effectiveness in counseling about hearing aids use, promoting maximum auditory performance, satisfaction and benefit to users.
Keywords: hearing; hearing loss; hearing aids; adult; protocols